Perkembangan Fisik Dan Mental Balita - Badriah, Laelatul (Literasi: Jurnal Ilmu Pendidikan, 2012)
This research is conducted to know growth of physical and mental child, the subject at this research is Muhammad Lutfillah age 2 year, first child from two harmonious couple, problem formula which raised in this research is how growth of physical and mental specially at research object and generally age child two years and problem of any kind of faced a period of the age of two year.The method of data collection is observation, documentation and interview. The theory of this research is growth theories which isn't it psychology experts. The result of this research indicate that: (1). Growth of physical of Lutfillah natural is normal growth like growth children. (2). Growth mental natural Lutfillah of equal quality like the growth of physical of normal, but in growth bounce him can assess lutfi have excess and weakness. (3). Growth of social Lutfillah sosialization can be better, obideint and bright to malleable and attention of behaviour and others. Keywords: Growth, physical, mental.